How Can I Feel Safe at Home? Adolescents' Experiences of Family Violence in Ghana - Addae, Evelyn Aboagye; Tang, Lynn (Frontiers in Public Health, 2021)
Despite the implementation of various national legal frameworks and global policies such as the UN Convention on the Rights of the Child to combat violence against young people, family violence against young people is prevalent, especially in WHO African region. Although, research on child maltreatment, specifically, for young children has received considerable attention in Ghana recently, there is little research on adolescents' experiences of such family violence. In this paper, we report the experiences and perceptions of adolescents with respect to family violence they had suffered or witnessed, and analyze the socio-ecological factors and power dynamics at home that contribute to such violence. The study employs a qualitative approach and the data comprise focus group discussion with 56 adolescents from 14 schools in seven districts of Ghana. The findings show that several adolescents in Ghana feel unsafe at home. They experience physical, psychological, and sexual violence as well as exposure to intimate partner violence, exploitation, and neglect. These violent acts were severe, with dire consequences such as permanent impairment and suicide. Perpetrators include all types of carers. The violent acts are often surreptitious and poly-victimization is common. The results also reveal that three main socio-ecological factors perpetuate and legitimize family violence: patriarchy, the normalization of corporal punishment as a method of child discipline, and superstitious beliefs about health. In general, carers demonstrate their superiority and control over the adolescents in an authoritarian manner, thereby, making the adolescents powerless. Implications of the study for policy and practice are discussed.